2003
DOI: 10.1063/1.1600842
|View full text |Cite
|
Sign up to set email alerts
|

Excitation fluence dependence of terahertz radiation mechanism from femtosecond-laser-irradiated InAs under magnetic field

Abstract: The excitation fluence and magnetic field dependence of terahertz (THz) radiation power from InAs is investigated. At low excitation fluence, an enhancement of the THz-radiation power is observed independent of the magnetic-field direction. As the excitation fluence is increased, a crossover of the terahertz radiation mechanism is observed. At excitation fluence above this crossover, the radiation power is either enhanced or reduced depending on the magnetic-field direction. These results are explained by cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…A much sharper decrease is observed in InAs as opposed to n-GaAs since diffusion and photoDember effects more sensitive to the carrier densities than drift effects. The predicted fluence dependence is found to be in excellent agreement with experimental data by Takahashi et al 8 plotted as an inset of Figure 9.…”
Section: A) B)supporting
confidence: 86%
“…A much sharper decrease is observed in InAs as opposed to n-GaAs since diffusion and photoDember effects more sensitive to the carrier densities than drift effects. The predicted fluence dependence is found to be in excellent agreement with experimental data by Takahashi et al 8 plotted as an inset of Figure 9.…”
Section: A) B)supporting
confidence: 86%
“…The pump beam was incident to the sample surface at Brewster angle and the spot size of the pump beam was 3 mm for the power measurements and 2 mm for the waveform measurements. Figure 1 shows the excitation density dependence of the THz-radiation power under magnetic fields of 0, ±2 T. The enhancement of the radiation power is observed under a magnetic field of ±2 T as reported previously [3]. The anomalous dependence was observed at ~ 1 |iJ/cm^, at which the radiation powers for B = 0 and ±2 T are crossing.…”
Section: Experimental Iviethodssupporting
confidence: 78%
“…Recently, an enhancement of the THz radiation power from InAs surface by applying a magnetic field has been reported by Sarukura et al [1], and several groups reported the radiation mechanism from InAs surface under a magnetic field [1][2][3]5]. The enhancement by the magnetic field is induced by Lorentz force, which modifies the direction of the photocurrent [3]. However, there is no complete understanding of the THz radiation mechanism especially under a magnetic field at high-density excitation.…”
Section: Introductionmentioning
confidence: 99%
“…In one typical technique, terahertz radiation is generated via a surface current transient ͑surface depletion field plus photo-Dember effect͒ or the optical rectification effect by illuminating semiconductor surfaces with ultrashort ͑Ͻ100 fs͒ pulses of near-infrared ͑NIR͒ radiation. [1][2][3][4] This technique allows terahertz timedomain spectroscopy via a pump-probe arrangement with the technologically desirable features of phase-coherent detection, high signal-to-noise ratios, and room-temperature operation. However, until now the radiation characteristics ͑the absolute power or the spectral bandwidth͒ of the signals generated by ultrashort pulses have not been compared to that of conventional thermal sources.…”
Section: Introductionmentioning
confidence: 99%